2019
DOI: 10.3390/su11102896
|View full text |Cite
|
Sign up to set email alerts
|

A Sustainable Transport Competitiveness Analysis of the China Railway Express in the Context of the Belt and Road Initiative

Abstract: The implementation of China’s Belt and Road Initiative macro strategy has promoted exchanges and cooperation between China and Europe and countries along the route. The operation of the China Railway Express provides a new transportation platform for China–Europe trade. The sustainable development of the China Railway Express has a great significance in terms of promoting the growth of China–Europe trade and meeting the demand for freight in Asia and Europe. Its time-saving advantage over shipping and its econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…The results showed that government subsidy for CR Express operators contributed to decreasing 60% of CR Express freight cost. Li et al [3] studied the competitiveness of the CR Express and pointed out that CR Express relied on a great deal of subsidies from local government and the market share of CR Express would be affected with a reduction Sustainability 2020, 12, 2083 5 of 16 in subsidies, which would have a negative impact on the sustainable development of CR Express. Wang et al [4] analyzed the current situation that most CR Express routes would find it difficult to remain operational without subsidy from the local government and proposed a "hub-and-spoke" organizational model of CR Express to generate scale economies and reduce costs.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that government subsidy for CR Express operators contributed to decreasing 60% of CR Express freight cost. Li et al [3] studied the competitiveness of the CR Express and pointed out that CR Express relied on a great deal of subsidies from local government and the market share of CR Express would be affected with a reduction Sustainability 2020, 12, 2083 5 of 16 in subsidies, which would have a negative impact on the sustainable development of CR Express. Wang et al [4] analyzed the current situation that most CR Express routes would find it difficult to remain operational without subsidy from the local government and proposed a "hub-and-spoke" organizational model of CR Express to generate scale economies and reduce costs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Collected from the references [1], the relevant information of the three modes of transportation is shown in Table 2. We collected the data of container number transported by CR Express (Wuhan-Alataw Pass-Hamburg) in the last 4 years from Wuhan Asia-Europe Logistics (www.wae-logistics.com) and operating cost from references [1,3], as shown in Table 3. To determine the value of parameters, we assume that the operational effort level (parameter a) increased slowly from 0.4 to 0.55 with the development of CR Express in the last four years.…”
Section: Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, base price 1 is about 98$/FEU, base price 2 is about 0.4$/FEU·km. (Data from national policy documents).Considering CR Express reaches European countries through Moscow of Russia, we take "Xi'an (or Zhengzhou)-Alashankou-Moscow" as the transportation route selected in this paper (Li et al, 2019). Therefore, the railway transportation fee paid by the land port company (Xi'an) to china railway container company is In general, domestic consignors often choose the way of highway transportation to transport the cargo to the departure center station of CR Express.…”
Section: ) Value Of Location a And B For Two Land Port Companies Amementioning
confidence: 99%
“…It is interesting to emphasize the high potential for energy recovery in these trains. This potential could justify the need for a change in transportation freight shares and the stimulation of intermodal services, both at national or international levels, for instance in Poland [3], or the OBOR initiative China-Europe [4]. Some results of the simulation for freight trains are presented in Table 11.…”
Section: Freight Transport With S-334 and S-252mentioning
confidence: 99%